Ultrasonic process tomographic imaging sensor: An approach utilising transceivers method - Mohd Hafiz, Fazalul Rahiman; Zulkarnay, Zakaria; Ruzairi, Abdul Rahim (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org